PERAN MEDIASI SELF EFFICACY DALAM PENERAPAN DIGITAL MARKETING, FINANCIAL LITERASI DAN FINANCIAL INCLUSION UNTUK MENINGKATKAN BUSINESS PERFORMANCE UMKM - Nugroho, Mahfud; Kuwatno, Kuwatno; Saraya, Sitta (JURNAL ILMIAH EDUNOMIKA, 2024)
The end of the Covid-19 pandemic requires MSMEs to sell their products through digital media. MSMEs which are still weak financially and literately cannot face competition in the digital market. Moreover, currently in the digital market there are many traders or large companies who also carry out retail sales directly to consumer users. So MSMEs have to face unfair competition. The aim of this research is to analyze the impact of using digital marketing, easy access to financial institutions (financial literacy) and financial literacy on improving MSME business performance. This research is quantitative research by analyzing causality. The number of respondents in this research was 100 MSMEs. Taken from MSMEs spread across Kendal Regency using the purposive sampling method. The data analysis method uses linear regression analysis with the help of the SmartPLS application. The research results show that digital marketing influences MSME business performance. Digital Marketing influences Self Efficacy. Financial inclusion influences MSME business performance. Financial inclusion affects self-efficacy. Financial literacy influences MSME business performance. Financial Literacy influences Self-efficacy. Self-efficacy influences MSME business performance. Self-efficacy cannot mediate digital marketing, financial literacy and financial inclusion on business performance in MSMEs. Financial literacy has no effect on MSME business performance. Ease of access to finance influences MSME business performance. Self-efficacy has no effect on MSME business performance,